2008
DOI: 10.1111/j.1551-2916.2008.02325.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Machining Method on the Catalycity and Emissivity of ZrB2 and ZrB2–HfB2‐Based Ceramics

Abstract: The emissivity and the catalytic efficiency related to atomic oxygen recombination were investigated experimentally in the range 1000-2000 K for ZrB 2 and ZrB 2 -HfB 2 -based ceramics. In order to evaluate the effect of the machining method, two series of samples, one prepared by electrical discharge machining and the other machined by diamond-loaded tools, were tested. High emissivity (about 0.7 at 1700 K) and low recombination coefficients (on average 0.08 at 1800 K) were found for all the materials. The exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
35
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 62 publications
(41 citation statements)
references
References 36 publications
5
35
1
Order By: Relevance
“…Metals, on the other hand, have much higher recombination coefficients, usually between 0.1 and 1 [18,19]. Numerous studies on recombination of O atoms to parent molecules (O 2 ) have been performed [19,20], but to the best of our knowledge, no attempt has been done to measure the coefficient for heterogeneous surface recombination of CO and O atoms. Quite a few attempts have been done on quantification of the radical recombination on silicon dioxide materials.…”
Section: Discussionmentioning
confidence: 98%
“…Metals, on the other hand, have much higher recombination coefficients, usually between 0.1 and 1 [18,19]. Numerous studies on recombination of O atoms to parent molecules (O 2 ) have been performed [19,20], but to the best of our knowledge, no attempt has been done to measure the coefficient for heterogeneous surface recombination of CO and O atoms. Quite a few attempts have been done on quantification of the radical recombination on silicon dioxide materials.…”
Section: Discussionmentioning
confidence: 98%
“…An analysis of the surface of EDM machined samples has shown that the EDM induce a damage: the surface modifications seem more pronounced in material B due to its higher refractoriness. The SEM-EDS analyses upon the electrical discharged surfaces confirmed the formation of a partially oxidized thin layer, which in turn includes contaminants from the electrically active tools used for EDM 34) . Flexure strength measured upon samples machined with EDM showed a decreased mean value of about 26.4%, compared to that obtained from specimens machined with DLTs, the major reason for this being the micro-cracked surface layer induced by the action of the electrical discharges 32) .…”
Section: Machinability By Electrical Discharge Machiningmentioning
confidence: 83%
“…Both the UHTC composition A and B, were tested, in samples machined by diamond loaded tools (DLT) or by electrical discharge machining (EDM) in order to evaluate the effect of the surface finish on those properties 33), 34) . Figure 3 reports the evolution of the total hemispherical emissivity versus temperature for the four selected materials: A-EDM (dotted line), A-DLT (full line), B-EDM (bold dotted line) and B-DLT (bold dotted line with space).…”
Section: Emissivity and Catalycitymentioning
confidence: 99%
“…Direct measurements of hemispherical emissivity at elevated temperatures are difficult, and few such data are available in the literature for UHTC materials. The measurements of Scatteia et al 58,59 for ZrB 2 -15SiC-2MoSi 2 , ZrB 2 -15SiC, and ZrB 2 -15SiC-10HfB 2 composites are a notable exception. Emissivity values ranged from 0.49 to 0.81, depending on material composition, temperature, machining method, and ambient oxygen environment.…”
Section: Surface Propertiesmentioning
confidence: 93%